THE IMPORTANCE OF DETERMINING INTERLEUKIN-8 FOR THE DIFFERENTIAL DIAGNOSIS OF PYELONEPHRITIS AND CYSTITIS IN WOMEN WITH NEPHROLITHIASIS - A. L. Pavlov; D. G. Koren’kov (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2020)
The objective was to optimize the topical diagnosis of the inflammatory process in the kidney and bladder in women with urolithiasisMethods and materials. Examined were 31 women aged 25 to 65 y. o., hospitalized for exacerbation of chronic cystitis with urolithiasis. The comparison group consisted of 15 healthy people without a history of urological diseases. In urine taken  separately from the bladder and ureter, the level of pro-inflammatory interleukin 8 (IL 8) was determined by enzyme-linked immunosorbent assay.Results. With an isolated exacerbation of chronic cystitis in the urine taken from the ureters, the concentration of IL 8 ((39±7.6) pg/ml) did not go beyond the normal indicators ((35±7) pg/ml), while the content of this cytokine in the bladder exceeded the norm by at least 3 times ((120±3.5) pg/ml). With a combination of exacerbations of inflammation in the bladder and kidneys, the concentration of IL 8 in the bladder was about 10 times higher than the control values ((350±27) pg/ml), and in the ureter from the affected side, no less than 8 times ((280±16) pg/ml).Conclusions. A comparison of the content of IL 8 in urine from organs (kidneys, bladder) that are supposedly affected by the inflammatory process makes it possible to clarify the localization of the focus of inflammation in the urinary system.